Synonymic notes on Palaearctic and Oriental Scydmaenus (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2013)
The last two years brought surprising descriptions and nomenclatural changes in the tribe Scydmaenini of the ant-like stone beetles. Makhan & Ezzatpanah (2011) established a new genus Roepnarainius, clearly based on a misinterpretation of morphological characters. Another curious taxonomic decision was the placement by Tronquet (2012) of Scydmaenus perrisi Reitter, 1882 as a junior synonym of S. hellwigii (Herbst, 1792). Illustrations in that article suggest that the material studied by Tronquet was misidentified, and a superficial similarity of aedeagi in two other common European species of Scydmaenus led to erroneous conclusions. These two cases are commented on and verified in the present paper.